2015
DOI: 10.3168/jds.2014-9209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of including canola meal and supplemental iodine in diets of dairy cows on short-term changes in iodine concentrations in milk

Abstract: The dietary requirement for iodine is based on thyroxine production, but data are becoming available showing potential improvements in hoof health when substantially greater amounts of I are fed. Feeding high amounts of I, however, can result in the milk having excessive concentrations of I. Canola meal contains goitrogenic compounds that reduce the transfer of I into milk. We hypothesized that including canola meal in diets would allow high supplementation rates of I without producing milk with unacceptable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Dried distillers grains have been reported to contain rumen-available UFA, which can contribute to milk fat depression . Weiss et al (2015) reported milk fat to linearly increase from 3.28 to 3.34% when canola meal in the diet was increased from 3.9 to 13.9% and fed to Holstein dairy cattle. The results of our study suggest that milk fat can be maintained when DDGS containing varying crude fat levels and canola meal are replace corn and soybean meal at 10% of the diet.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Dried distillers grains have been reported to contain rumen-available UFA, which can contribute to milk fat depression . Weiss et al (2015) reported milk fat to linearly increase from 3.28 to 3.34% when canola meal in the diet was increased from 3.9 to 13.9% and fed to Holstein dairy cattle. The results of our study suggest that milk fat can be maintained when DDGS containing varying crude fat levels and canola meal are replace corn and soybean meal at 10% of the diet.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Nudda et al [ 6 ] reported that the iodine supplementation in dairy goat diets doubled the milk iodine content when compared with the control group, even if no evident effect was observed in the gross composition of milk. On the contrary, Weiss et al [ 7 ] found that iodine concentration increased in serum but not in milk after supplementation of this element in diets of dairy cows. In fact, very little information is available about the effects of iodine addition on ewes’ milk and milk-based product composition, nor about the response of dairy product microbiota.…”
Section: Introductionmentioning
confidence: 98%
“…Changes in animal feeding have been proposed as one of the most promising approaches to modify iodine content in milk [ 5 ]. Some studies [ 6 , 7 ] have been carried out to evaluate the effects of dietary iodine supplementation in dairy goats and cows on milk iodine content and milk production traits. Nudda et al [ 6 ] reported that the iodine supplementation in dairy goat diets doubled the milk iodine content when compared with the control group, even if no evident effect was observed in the gross composition of milk.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of these food sources to total iodine intake may be slightly overstated, as they do not account for iodine from supplements, water, or iodized salt, which can contribute between 10–20% of iodine intake [ 14 ]. The iodine content in dairy milk can vary widely [ 15 ], depending on the iodine content in cattle feed, teat-dipping practices before and after milking [ 16 ], and the presence of goitrogens (substances that can block the uptake or utilization of iodine in cattle feed [ 17 ]). Other common food sources of iodine include grains and eggs [ 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%